Integrative Active Learning and Critical Thinking Development in Indonesian Higher Education: A Quasi-Experimental Study - Besse Qur'ani; Israwati Hamsar (Academic Bright Collaboration, 2025)
Critical thinking is widely recognized as an essential competency in higher education, particularly in disciplines that require analytical reasoning and contextual problem-solving. This study investigated the effect of an integrative active learning approach on the development of critical thinking skills among undergraduate students in the Family and Consumer Sciences Education program at an Indonesian university. A quasi-experimental design with a nonequivalent control group was employed involving 60 students divided into experimental and control groups. The intervention integrated group discussions, problem-based learning (PBL), and structured presentations supported by basic instructional technology, including projectors and presentation software, while the control group received conventional lecture-based instruction. Data were collected using an adapted critical thinking instrument measuring five dimensions: analysis, inference, evaluation, explanation, and interpretation. The results of the paired sample t-test indicated a substantial improvement in the experimental group (p = 0.000), whereas the control group also demonstrated a statistically significant but smaller gain (p = 0.032), suggesting that conventional instruction may still contribute to incremental critical thinking development. An independent sample t-test further revealed a significant difference between the post-test scores of both groups (p = 0.000). The calculated Cohen’s d value of 1.94 indicated a very large intervention effect, although this finding should be interpreted cautiously considering the short intervention duration and limited sample size. Unlike many previous studies that focus on isolated active learning strategies or technology-intensive environments, this study examines the implementation of an integrative active learning framework within a resource-constrained higher education context. The findings suggest that structured active learning supported by modest technological resources can effectively promote critical thinking development in Indonesian higher education settings.